THE TRACER STUDY OF KPI STUDY PROGRAM ALUMNI 0F STID MOHAMMAD NATSIR - AAN HANDRIYANI (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
This tracer study research includes alumni of STID KPI Study Program Mohammad Natsir from 2004 - 2021 which aims to obtain an overview of the absorption of KPI alumni in the world of da'wah and work including the waiting period to get a job, type of work and suitability of work with competence as well as to explain feedback ( feedback) from alumni related to learning factors that are considered most beneficial for alumni development in the world of da'wah and work, in this study also described the competencies obtained by alumni during their studies. This research is included in the type of descriptive-quantitative research through a survey approach which includes three stages; 1) Development of concepts and instruments; 2) Data collection; 3) Data analysis and reporting. The sampling method is random, with a proportion of 14% according to the number of graduates. The type of data collected in this study is primary data obtained directly from alumni through a structured questionnaire. Questionnaires were distributed via Google forms which were distributed directly to alumni online starting on October 15, 2021 to November 15, 2021. The results showed that most of the alumni of the STID KPI study program Mohammad Natsir got jobs with a waiting period of less than 3 months, and the competence of alumni was very high. high in various aspects, except for English skills which must be further improved.